Perbedaan Kadar Asam Urat Yang Diperiksa Segera Dengan Disimpan 24 Jam Pada Suhu Ruang - Devita Kumala Dewi; Anak Agung Eka Cahyani; Sri Idayani (Journal of Medical Laboratory Research, 2025)
Laboratory examination plays a crucial role in establishing the diagnosis of disease. However, uric acid samples may undergo a decrease in concentration during storage due to alterations in protein levels. Such changes can be detected through laboratory testing and may gradually reduce the proportion of protein over the course of storage. Serum storage in the laboratory may be performed at room temperature. To maintain sample stability, storage is recommended at 20°C–25°C for up to five days.This study aimed to evaluate the difference in uric acid levels between serum analyzed immediately after collection and serum stored for 24 hours. An experimental design was employed, involving a total of 19 samples. Serum was examined both immediately after collection and following 24-hour storage at room temperature. Primary data were analyzed using descriptive and statistical methods, including data distribution tests and the Paired T-Test. The findings indicated that there was no significant difference in the mean uric acid levels between samples analyzed immediately and those stored for 24 hours at room temperature.It is therefore essential that prior to conducting any examination, careful attention is given to specimen handling and that all procedures strictly adhere to standard operating protocols (SOPs). This ensures reliable results and prevents potential adverse consequences for patients in the future.